PENGARUH MEDIA SOSIAL, EDUKASI PASAR MODAL DAN PENGGUNAAN ANALISIS FUNDAMENTAL TERHADAP KEPUTUSAN INVESTASI DI PASAR MODAL : STUDI PADA MASASISWA INVESTOR SAHAM DI SURABAYA - Setiawati, Alifia Arum; Venusita, Lintang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to examine the influence of social media, capital market education, and the use of fundamental analysis on capital market investment choices made by student stock investors in Surabaya. Questionnaires were distributed to students from various universities in Surabaya who actively invest in the capital market. Purposive sampling was used to select 400 respondents as the sample for this research. This research uses a quantitative methodology with the Partial Least Squares (PLS) technique, and the SmartPLS application is used for analysis. Research findings show that social media has a significant influence on students' investment decisions. Capital market education has a significant influence on investment decisions. Apart from that, the use of fundamental analysis also shows a significant influence on student investment decisions